Harum madu dan dupa kemenyan di Jawa Tengah - Goloubinoff, M. (Yayasan Obor Indonesia, 2002)
In North Sumatra, Batak farmers tap benzoin resin from several species of Styrax. Most of the production is sent to Central Java where it is used for incense and traditional cigarettes manufacture. Consummation of klembak menyan, a traditional cigarette has decreased because of competition of kretek industry. Incense factories are located in the South. They manufacture blocks of incense made of benzoin mixed with other ingredients like damar. Javanese people still burn often benzoin during traditional ceremonies. Incense is actually main end use of the resin either on domestic or international market. Some benzoin is exported to India and Arabic countries via Singapore. Pharmacy and perfume industries in Europe also use small quantities of benzoin.